Pengaruh Carbon Emission Disclosure dan Corporate Social Responsibility terhadap Financial Performance Perusahaan Manufaktur di Indonesia - Rudiansyah Yuliatma; Dina Maria Kristari (Sekolah Pascasarjana Perbanas Jakarta, 2022)
The purpose of this study was to examine the effect of carbon emission disclosures (CED) and corporate social responsibility (CSR) on the financial performance of manufacturing companies in Indonesia. This study uses secondary data obtained from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. Multiple regression panel data is used to see the effect between variables using SPSS. The results showed that CED had a significant negative effect on FP and CSR had no significant effect on FP. In addition, CED and CSR simultaneously have an influence on FP.